Prevalence of asthma and atopy in italian olympic athletes - Maiolo, C.; Fuso, L.; Todaro, A.; Anatra, F.; Boniello, V.; Basso, S.; de Lorenzo, A.; Pistelli, R. (International Journal of Sports Medicine, 2004)
This study aimed to assess the prevalence of asthma and atopy in the Italian athletes who were trying for a position on the Italian Olympic team for the 2000 Sydney Olympic Games. Overall, 1060 athletes (mean age 24 years, range 15 - 69 years, 729 males) were recruited and divided into three groups of sport activities: 1) anaerobic, 2) aerobic-anaerobic, 3) aerobic. Asthmatic and atopic athletes were identified by a self-administered, standardized questionnaire modified from the ISAAC questionnaire. Spirometry was performed in the athletes who reported wheezing or asthma and in an equal number of randomly selected controls. Athletes reporting wheezing or asthma were 15 %. However, only a minority of asthmatics had moderate or severe disease: indeed, 2.5 % reported more than 4 attacks in the last year. The prevalence of atopy was 18 %. Asthma was more common in athletes engaged in aerobic sport activities than in the other groups. Asthmatic athletes had a significantly lower value of some spirometric parameters in comparison with the control group. In conclusion, the prevalence of wheezing or asthma in a large sample of Italian competitive athletes was found higher than in general population; respiratory symptoms were more prevalent in athletes engaged in aerobic sport activities; a significant impairment of lung function was found in athletes suffering from mild and rarely symptomatic asthma.